(3dehGLgI GdCReI GdeGdjI GdYGdejIs - (3aQjO(B, (3GdfLGQs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2009)
(3YQV GdGReI GdeGdjI GdYGdejI h GdcSGO GdYGdej GdLOjO , GdJMOjGJ GdeYGUQI h GdGReI GdeGdjI GdYGdejI , GdJfGaSjI GdeYGUQI h CReI GdKbI aj GdfXGe GdGbJUGOj GdYGdej , GgejI JWhjQ GdHjFI GdYQHjI dehGLgI GdJMOjGJ , bjGOI GdJZjjQ GdYQHj , egGQGJ GdJZjjQ GdGSJQGJjLj GdYQHj eY GdJWQb Gdi eDTQGJ GdJZjjQ EOGQI HQGeL GdJZjjQ h GdGSQGY GdGSJQGJjLj GdJfejI GdJfXjejI h JLOjO GdefXeGJ GdYQHjI , GdJhLgGdYQHj GdLOjO aj GdbQf (B21 (3,GdNWI GdGSJQGJjLjI dehGLgI GdGReI GdeGdjI GdYGdejI , JWHjb GdNWI GdGSJQGJjLjI HGdPcGA GdSdhcj, EYGOI gfOSI GdeDSSGJ h GdGYeGds
(3eQGLY U(B.411 (3;bGFeI GdGTcGd U(B.11s
Keywords: (3GdGReI GdeGdjI GdYGdejIs; (3GdJMhdGJ GdEbJUGOjIs; (3GdYhdeIs